Molecular Changes Underlying Hypertrophic Scarring Following Burns Involve Specific Deregulations at All Wound Healing Stages (Inflammation, Proliferation and Maturation) - Čoma, Matúš; Fröhlichová, Lucia; Urban, Lukáš; Zajíček, Robert; Urban, Tomáš; Szabo, Pavol; Novák, Štěpán; Fetissov, Vitaly; Dvořánková, Barbora; Smetana, Karel; Gál, Peter (International journal of molecular sciences, 2021)
Excessive connective tissue accumulation, a hallmark of hypertrophic scaring, results in progressive deterioration of the structure and function of organs. It can also be seen during tumor growth and other fibroproliferative disorders. These processes result from a wide spectrum of cross-talks between mesenchymal, epithelial and inflammatory/immune cells that have not yet been fully understood. In the present review, we aimed to describe the molecular features of fibroblasts and their interactions with immune and epithelial cells and extracellular matrix. We also compared different types of fibroblasts and their roles in skin repair and regeneration following burn injury. In summary, here we briefly review molecular changes underlying hypertrophic scarring following burns throughout all basic wound healing stages, i.e. during inflammation, proliferation and maturation.
Keywords: Wound Healing; extracelulární matrix; Extracellular Matrix; Inflammation; Humans; proliferace buněk; Cicatrix, Hypertrophic; Cell Proliferation; lidé; zánět; jizva hypertrofická; Epithelial Cells; popálení; epitelové buňky; Burns; fibroblasty; Fibroblasts; hojení ran